Copulative Model of Word Formation in Modern Chinese Language - Abdullaevna, Hashimova Sabohat (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the copulative model of word formation in modern Chinese language. The article discusses the features of the formation of words and word constructions, formed according to this model. In the study methods such as analysis, synthesis, and component analysis were used. The article provides relevant conclusions on this topic.